Knowledge, Attitude and Practice of Hand washing among Street vendors in Campus of Universitas Padjadjaran, West Java from June-November 2012 - Tajul Al Adib; Ardini S. Raksanagara; Dewi Hawani; Elsa Pudji Setiawati (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Hand washing is a moderate step in preventing communicable diseases. Communicable diseases like diarrhea and respiratory tract infection can be reduced significantly just by practicing hand washing. Most of the people already knew how to wash their hand, but some of them still did not understand the objective and the correct ways of performing hand washing. The aim of the study was to evaluate knowledge, attitude and practice of hand washing among street vendors.Methods: A descriptive study was conducted to 30 street vendors at the gate of Universitas Padjadjaran Campus from June to November 2012. The inclusion criterias were street vendors involved in food preparation, cooking, mixing, and willing to participate in this study. A questionnaire was developed to identify the knowledge, attitude and practice of hand washing. The level of the variable measured was divided into 3 categories: good, moderate, and poor. The collected data were analyzed and presented in table.Results: There were 12/30 of street vendors classified as having moderate knowledge and 25/30 as having good attitude and good practice of hand washing.Conclusions: The street vendors at the gate of Universitas Padjadjaran Campus had moderate knowledge, good attitude and good practice of hand washing. DOI: 10.15850/amj.v2n3.500